Seeding the future – the issues of supply and demand in restoration in Australia. (January 2015) - Broadhurst, Linda; Driver, Martin; Guja, Lydia; North, Tom; Vanzella, Bindi; Fifield, Graham; Bruce, Stephen; Taylor, David; Bush, David
Summary It has been almost 15 years since concerns about the limited capacity of remnant native vegetation to supply the volumes of seed required to meet increasing restoration demands were first raised. Since that time little progress has been made towards addressing this constraint with the ongoing decline of native vegetation communities, especially since 2000, further challenging seed supply. We provide examples of the size of this demand for seed, as well as major issues associated with seed sourcing. We also discuss how invoking the concept of market forces to drive seed supply and demand is inappropriate and highlight the need for an industry body to oversee seed collection and utilisation standards. We further propose key actions that are required to secure the seed supply chain within the next 20 years to meet existing and future restoration targets. We argue that concerted, coordinated action at Commonwealth, State and regional levels are required to underpin effective future restoration outcomes.